The Hate U Give Readers Guide - Kansas State University, K-State First (My University, 2018)
This short reading guide was distributed during Orientation and Enrollment and provided a starting point as students read through “The Hate U Give” by Angie Thomas. The guide provides questions and themes for readers to consider as they read the book.
Citation: K-State First (2018). The Hate U Give Readers Guide. Brochure. Kansas State University, Manhattan, KS.
Keywords: Hate U Give, The; Common reading program; Brochures; Guide; First-year experience program; Promotional materials